The Relationship between Sarcoidosis of Intrathoracic Lymph Nodes and Digestive System Diseases: A Comparative Observation - A.V. Medvedev (Journal of Global Pharma Technology, 2017)
Background: The cases of sarcoidosis of intrathoracic lymph nodes often accompanied by various digestive system diseases have not received enough attention in medical publications. Therefore, the objective of this study is to explore the interrelatedness between the development of gastrointestinal disorders and pulmonary pathology. Materials and methods: The study included 79 patients with sarcoidosis of intrathoracic lymph nodes (ITLN), mean age 46.4±0.9, disease duration 6.8±0.4 years. The patients studied were divided into two groups: patients with ITLN sarcoidosis with gastrointestinal (GI) tract diseases, and people with ITLN sarcoidosis with no symptoms of gastrointestinal tract diseases. All patients underwent laboratory and instrumental examination. Results: Diseases of the digestive system were found in 19 patients with ITLN sarcoidosis. Newly diagnosed digestive system diseases were observed in four patients: one patient with duodenal ulcer, three patients with gastroesophageal reflux disease (GERD). Exacerbation of previously diagnosed diseases was recorded in fifteen patients; most often it was exacerbation of chronic gastritis and chronic duodenal ulcer (five cases each), in three patients it was exacerbation of chronic cholecystitis, in two patients exacerbation of chronic pancreatitis and chronic gastric ulcer was detected. Conclusion: The development of gastrointestinal diseases coincides in time with the development of sarcoidosis or occurs under conditions of its treatment. In patients with sarcoidosis who underwent therapy of this disease, gastrointestinal diseases were observed in 55.5% of patients, in patients with recurrent, progressive course of sarcoidosis they were observed 1.4 times more often than in those with steady course of sarcoidosis. Keywords: Sarcoidosis of Intrathoracic Lymph Nodes (ITLN Sarcoidosis) – Gastrointestinal Diseases-Digestive System Pathology.